2018
DOI: 10.1016/j.ijpharm.2018.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of melibiose and trehalose as stabilising excipients for spray-dried β-galactosidase formulations

Abstract: Spray-dried protein formulations commonly require stabilising excipients to prevent protein degradation during processing and storage, and trehalose has been commonly used. The purpose of this work was to evaluate melibiose in spray-dried protein formulations in comparison to trehalose. The protein-activity-preserving efficacy, process behaviour and storage stability were studied. Spray drying of β-galactosidase was carried out using different process temperature, drying air flow and feed liquid atomisation se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In fact, it has been well established that trehalose is known to be a superior stabilizer in providing protection to biological materials against dehydration and desiccation, in comparison with a number of other sugars, especially during lyophilization, spray drying and exposure to high temperatures in solution (Lipiainen et al, 2018;Rajagopal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been well established that trehalose is known to be a superior stabilizer in providing protection to biological materials against dehydration and desiccation, in comparison with a number of other sugars, especially during lyophilization, spray drying and exposure to high temperatures in solution (Lipiainen et al, 2018;Rajagopal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…β-Galactosidase formulated with trehalose by freeze-drying was found to be the most stable formulation when compared with other sugars (i.e., dextran 70 kDa, dextran 6 kDa and inulin) [16]. In a study by Lipiäinen et al [29], melibiose or trehalose was used as stabilizing excipient for β-galactosidase by spray drying, and its activity remained for 30 days at 40 • C.…”
Section: Enzymatic Activity Of β-Galactosidasementioning
confidence: 97%
“…erythritol, glucosamine, and xylitol) were found only in one study each. [48,100,128] Even though mannitol is one of the most well-used sugars in commercialized biologic products, [141] when used alone to spray-dry certain classes of proteins (e.g. mAbs), its crystallization during processing has shown the potential to deleteriously affect product stability.…”
Section: Monosaccharidesmentioning
confidence: 99%
“…However, lactose and melibiose are reducing sugars, so their free aldehyde groups can undergo the Maillard reaction when in contact with the amino groups of proteins. [22,48,136] Although, the reducing disaccharides have been extensively selected to study protein spraydrying [17,22,24,44,48,51,80,81,83,84,86,94,111,128,131,144] and are used in some marketed bio-formulations, [141] it is crucial to guarantee that no detrimental chemical interaction takes place, during processing and storage. Within a spray-drying context, it has been reported that trehalose could be more successful than other sugars, when stabilizing proteins.…”
Section: Disaccharidesmentioning
confidence: 99%